MIDWIVES' KNOWLEDGE OF OXYTOCIN USE DURING SPONTANEOUS LABOR: A QUASI-EXPERIMENTAL STUDY IN FIVE BASIC MATERNITY UNITS IN KINDU, DEMOCRATIC REPUBLIC OF CONGO - Alain, Bakangana Mungu; Onyango O, Rosebella; Bogren, Malin; Katumba, Kitingi (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2022)
The purpose of this study was to assess midwives' knowledge of oxytocin use during spontaneous labor. It was a quasi-experimental study conducted with a comprehensive sample of 14 midwives from five basic maternity hospitals in Kindu, divided into two groups: an intervention group and a control group. To assess the level of knowledge, we developed a two-part knowledge test (the first part was composed of socio-demographic characteristics and the second part consisted of 10 questions on knowledge).  We referred to the threshold of Debesse and Milalaret (1968) below:- Less than 60% = low level of knowledge;- From 60 to 79,99% = average level of knowledge and;- 80% and more = high level of knowledgeThe data were processed and analyzed using STATA 14 software. The data grouped into classes were scored on a maximum of 20 points and analyzed using the central tendency and dispersion indices. After analysis, it was found that the performance of midwives in the Kindu base maternity units on a knowledge test on the use of oxytocin during spontaneous labor was inadequate before the training (43%), well below the 60% threshold for average performance. In other words, the training improved midwives' knowledge of oxytocin use during spontaneous labor by increasing performance from 43% to 79.28%.